Memory rehabilitation for people with multiple sclerosis - das Nair, Roshan; Martin, Kristy-Jane; Lincoln, Nadina (Cochrane Collaboration, 2016)
Background: This is an update of the Cochrane review ‘Memory rehabilitation for people with multiple sclerosis’ (first published in the Cochrane Library 14 March 2012, Issue 3). Impairments in cognitive function, particularly memory, are common in people with multiple sclerosis (MS) and can potentially affect their ability to complete functional activities. There is evidence from single-case or small group studies that memory rehabilitation can be beneficial for people with MS, but findings from randomised controlled trials (RCTs) and systematic reviews have been inconclusive. Objectives: To determine whether people with MS who received memory rehabilitation showed: 1. better outcomes in their memory functions compared to those given no treatment or receiving a placebo control; and 2. better functional abilities, in terms of activities of daily living, mood, and quality of life, than those who received no treatment or a placebo. Search methods: We searched the Trials Specialised Register of the Cochrane Multiple Sclerosis and Rare Diseases of the CNS Group (2 June 2015) and the following electronic databases: The NIHR Clinical Research Network Portfolio database (NIHR CRN) (from 2010 to June 2015), The Allied and Complementary Medicine Database (AMED) (2010 to June 2015), British Nursing Index (BNI) (2010 to June 2015), PsycINFO (2011 to June 2015), and CAB Abstracts (2010 to June 2015). Start dates for the electronic databases coincided with the last search for the previous review. We handsearched relevant journals and reference lists. Selection criteria: We selected RCTs or quasi-randomised trials ofmemory rehabilitation or cognitive rehabilitation for people with MS in which a memory rehabilitation treatment group was compared to a control group. Selection was conducted independently first and then confirmed through group discussion. We excluded studies that included participants whose memory deficits were the result of conditions other than MS unless we could identify a subgroup of participants with MS with separate results. Data collection and analysis: Three review authors were involved in this update in terms of study selection, quality assessment, and data extraction. We contacted investigators of primary studies for further information where required. We conducted data analysis and synthesis in accordance with the Cochrane Handbook for Systematic Reviews ofInterventions (Higgins 2011). We performed a ’best evidence’ synthesis based on the methodological quality of the primary studies included. Main results: We added seven studies during this update, bringing the total to 15 studies, involving 989 participants. The interventions involved various memory retraining techniques, such as computerised programmes and training on internal and external memory aids. Control groups varied in format from assessment-only groups, discussion and games, non-specific cognitive retraining, and attention or visuospatial training. The risk of bias of the included studies was generally low, but we found eight studies to have high risk of bias related to certain aspects of their methodology. We found significant effect of intervention on objective assessments of memory in both the immediate and long-term follow-ups: standardised mean difference (SMD) 0.23 (95% confidence interval (CI) 0.05 to 0.41) and SMD 0.26 (95% CI 0.03 to 0.49), respectively. We also found significant effect of intervention for quality of life in the immediate follow-up (SMD 0.23 (95% CI 0.05 to 0.41)). These findings showed that the intervention group performed significantly better than the control group. We also found a significant difference for activities of daily living (ADL) in the long-term follow-up (SMD -0.33 (95% CI -0.63 to -0.03)), showing that the control groups had significantly less difficulty completing ADLs than the intervention groups. We found no significant effects, either immediate or long-term, on subjective reports of memory problems (SMD 0.04 (95% CI -0.19 to 0.27) and SMD 0.04 (95% CI -0.19 to 0.27)); on mood (SMD 0.02 (95% CI -0.16 to 0.20) and SMD -0.01 (95% CI -0.21 to 0.20)); and on immediate follow-up for ADL (SMD -0.13 (95% CI -0.60 to 0.33)) and in the long term for quality of life (SMD 0.16 (95% CI -0.03 to 0.36)). We could not complete a sensitivity analysis of intention-to-treat in comparison with per-protocol analysis, due to insufficient information from the included papers. However, a sensitivity analysis of high- versus low-risk studies suggested that while quality of the trials did not affect most outcomes, differences were seen in the objective memory outcomes (both at immediate and long term) and quality of life (immediate) outcome, with studies with higher risk of bias inflating the overall effect size estimates for these outcomes, and the test of overall effect changing from being statistically significant to not significant when studies at high risk of bias were excluded. This suggests that lower-quality studies may have positively influenced the outcomes. Authors’ conclusions: There is some evidence to support the effectiveness of memory rehabilitation on memory function, as well as on quality of life. However, the evidence is limited and does not extend to subjective reports of memory functioning or mood. Furthermore, the objective measures used are not ecologically valid measures, and thus potentially limit generalisability of these findings into daily life. Further robust RCTs of high methodological quality and better quality of reporting, using ecologically valid outcome assessments, are still needed.